Literary Transfer between Peripheral Languages: A Production of Culture Perspective - Hacohen, Ran (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2014)
Literary translations from Hebrew into Dutch and vice versa between 1991 and 2010 are examined as a test case for cultural transfer between two peripheral languages, using a production of culture perspective (Peterson and Anand 2004). The findings show 138 Dutch books translated from Hebrew against 52 Hebrew books translated from Dutch. The data are analyzed by genre, translator’s productivity, and number of books per author. The analysis reveals that both directions were similar in distribution of genres, but differed significantly in translator’s productivity (the productivity of the average Dutch translator is more than twice as high as that of his or her Hebrew counterpart) and in the number of translated titles per author (twice as many in the Dutch market). The discussion traces these differences to the different structure of the translation labour market in Israel as compared to that of the Netherlands and Belgium and to the dominance of Dutch state subsidy and Flemish Community subsidy in both directions of the transfer, however with a different policy of subsidy in each direction. It seems that significant conclusions can be reached by examining such factors as size and distribution of the corpus on the backdrop of labour conditions and state subsidy.